Spontaneous pregnancy after tracking ovulation during menstruation: A case report of a woman with premature ovarian insufficiency and repeated failure of in vitro fertilization - He, Ye; Wang, Wanlu; Wu, Chunmei; Li, Wenwen; Liu, Hongjiang; Wei, Zhaolian (Frontiers in Medicine, 2022)
The diagnosis of premature ovarian insufficiency (POI) is devastating in women of reproductive age because of the small chance of spontaneous pregnancy. Here, we report a very rare case with POI and repeated failure of in-vitro fertilization (IVF) but finally got pregnant naturally by following the guidance of having sexual intercourse during the menstruation as the ovulation was monitored. Estradiol valerate was treated to increase the thickness of the endometrium and stop the menstrual bleeding. 14 days after the ovulation, serum human chorionic gonadotropin (HCG) level was 208.44 IU/L. Later, a series of transvaginal ultrasounds also indicated normal-appearing intrauterine pregnancy. A healthy baby girl was delivered at term by means of cesarean section. Our report calls for that although the chance of spontaneous pregnancy is relatively low in POI patient with repeated IVF failures, as long as ovulation does occur and even it happens during the menstruation, natural pregnancy is still worth trying with a series of proper and personalized treatments.